Prevalence of anaemia in school-going adolescents of Vadodara district: A cross-sectional study - Ruhi Himanshu Agarwal; Kedar Gautambhai Mehta; Aishwarya Shreyas Parikh; Zalak Shitalbhai Shah; Paragkumar Chavda (Journal of Clinical and Scientific Research)
Background: Anaemia is a major public health problem. Anaemia in adolescence is an important risk factor and a serious detriment to the economic development of the country. We studied the distribution of haemoglobin (Hb) and prevalence of anaemia in school-going adolescents of urban and rural areas of Vadodara district, Gujarat. Methods: This cross-sectional study was conducted in 2023 amongst rural and urban school-going adolescents. It was conducted in six government schools (three from rural areas and three from urban areas). Sample for Hb testing was obtained by finger-prick method. Results: The prevalence of anaemia was 41.5% and 13.6% among adolescent girls and boys respectively. On classifying the severity of anaemia as per the World Health Organization criteria, of 77 females, 32 (41.5%) had anaemia; based on severity, 12 (37.5%) had mild, 17 (53.1%) had moderate and 3 had severe anaemia. Out of 52 males, 7 (13.6%) were anaemic; out of which 5 had mild and 2 had moderate anaemia. Almost 30% of school children were anaemic in urban areas and 40% of school children were in rural areas. Conclusions: This study showed that anaemia is more prevalent in adolescent girls than boys, and the prevalence of anaemia is slightly higher in rural adolescents than in urban adolescents. These data would be helpful in designing intervention programmes.